A study on the learning experience of visitors of digital museums in STEAM education: From the perspective of visitors’ visual evaluation - Zhang, Xin; Hu, Jieming (Frontiers in Psychology, 2022)
Public education in museums has the interdisciplinary nature of STEAM education contemporary learning. In the contemporary learning process of the public, digital museums can rely on mobile terminals to provide people with opportunities for mobile learning. Especially since the global outbreak of COVID-19, many offline museums have been forced to close their doors or impose restrictions. How to use digital museums to better carry out the learning experience of visitors is a problem worthy of attention. Effective dissemination of visual information can help digital museums conduct educational activities more efficiently. The purpose of this study was to explore a research method for visual evaluation of visitors’ learning experiences in digital museums. The visual evaluation of visitors in the digital museum learning experience involves the layout of exhibition content, the form of exhibition space, and the way of display of exhibits. Through eye-tracking engineering experiments, we obtain and analyze the visual data of visitors during the educational experience of the digital museum to form an accurate evaluation. This method can be used to assess the visual satisfaction of visitors with the educational experience of a digital museum in mobile learning. This kind of evaluation research can provide strong data support and design optimization direction guidance for the development of digital museum public education.